Diagnosis of Cutaneous Larva Migrans using Point of Care Ultrasound - Daniella Lamour; Robert A. Farrow; Jean Pierre; Paul Khalil (CINQUILL Medical Publishers Inc., 2024)
Larva is a cutaneous parasitic infection that occurs when an immature hookworm larva inadvertently penetrates the dermis of a human, typically on the extremities. Traditionally, a clinical diagnosis is made when a tortuous/ eruption is seen superficially in the skin with complaints of intense . Point of care ultrasound (POCUS) is a useful diagnostic tool for soft tissue complaints in the emergency department (ED). We describe a case of an 18-year-old woman who presented to the ED with foot four days after walking on the beach barefoot. POCUS examination revealed several motile structures in the dermis of the patient's foot, confirming our suspicion of cutaneous larva . The patient was then placed on an oral and her symptoms resolved shortly after.